New frontiers in artificial intelligence : JSAI-isAI 2016 Workshops, LENLS, HAT-MASH, AI-Biz, JURISIN and SKL, Kanagawa, Japan, November 14-16, 2016, revised selected papers /: JSAI-isAI 2016 Workshops, LENLS, HAT-MASH, AI-Biz, JURISIN and SKL, Kanagawa, Japan, November 14-16, 2016, revised selected papers. (2017) - Unknown
No abstract available